Effect of Work Environment, Work Motivation and Work Discipline on Teacher Performance at SD Plus Anbata - Suwardi, Suwardi; Bukhori, Moh; Karnawati, Tin Agustina (Journal of English Language and Education, 2026)
The importance of the teacher's role in learning impacts the quality of students. The purpose of this study was to determine whether the work environment, work motivation, and work discipline partially and simultaneously affect teacher performance at SD Plus ANBATA Medan. The method used was multiple linear regression, assisted by SPSS 26 software. The sampling method was saturated sampling using an online questionnaire, where all 34 teachers at SD Plus ANBATA Medan were used as samples in this study. The data to be analyzed must meet validity and reliability tests, as well as classical assumption tests such as normality, heteroscedasticity, and multicollinearity. The results showed that the work environment variable did not affect teacher performance at SD Plus Anbata Medan, while the work motivation and work discipline variables had a positive and significant effect on teacher performance at SD Plus Anbata Medan. The simultaneous results showed that the work environment, work motivation, and work discipline had a positive and significant effect on teacher performance at SD Plus ANBATA Medan.